Homoharringtonine: mechanisms, clinical applications and research progress - Wang, Wen; He, Lan; Lin, Ting; Xiang, Fulan; Wu, Yibin; Zhou, Fangliang; He, Yingchun (Frontiers in Oncology, 2025)
Homoharringtonine is a natural alkaloid with significant pharmacological potential that has demonstrated promising efficacy in the treatment of hematological malignancies in recent years. This article systematically reviews the pharmacological mechanisms of Homoharringtonine, focusing on its key roles in inducing apoptosis, inhibiting cell cycle progression, and reducing cell migration and invasion. Additionally, HHT exhibits multiple biological activities, including immunomodulation, antiviral effects, and anti-fibrotic properties, with recent studies also revealing its potential neuroprotective functions. In clinical trials, Homoharringtonine has demonstrated promising efficacy in the treatment of hematological malignancies, particularly in various types such as acute myeloid leukemia and chronic myeloid leukemia. Despite the significant antitumor effects observed in clinical applications, its low bioavailability and potential side effects remain major challenges that limit its widespread use. This article details the latest research advancements aimed at enhancing the bioavailability of Homoharringtonine, including various drug delivery systems such as nanoparticles and liposomes, as well as chemical modification strategies. These approaches not only improve HHT’s bioavailability in vivo but also enhance its targeting ability while reducing toxicity to normal cells. Furthermore, the combination of HHT with other drugs presents broader prospects for clinical treatment. By exploring the diverse pharmacological activities of Homoharringtonine in depth, this article aims to provide a foundation for developing novel therapeutic approaches based on natural products, thereby advancing HHT’s application research in cancer treatment and other fields.